AVALIAÇÃO DA SUSTENTABILIDADE DAS FORMAS DE USO E MANEJO DE MATAS CILIARES DO ALTO CURSO DO RIO PERICUMÃ, BAIXADA MARANHENSE - Braga, Klenya Rosa Rocha (2006)
Evaluation of the sustainability of riparian forests use and management forms from Pericumã River high course, Baixada Maranhense, becomes relevant because that plant formations constitute important ecosystems for conservation of the high course of this basin. So this work had the objective of evaluating the sustainability of the use and management forms, present situation and perspectives of conservation for the riparian forests from the Pericumã River high course, utilizing the phytosociology and the ethnobotany, in a associated and adapted methodology. Three sites were used for the study of phytosociology and ethnobotany. The existence of 96 species and 40 families was observed in the study area. Shannon-Wiener index was 3,29. From the formal and informal interviews joint to the community, seven ethnocategories were determined, among which the construction material was detached as the most quoted. The model of use of the riparian forests plant resources favors the loss of interesting species and the diverse use of the environments present in the local riparian zone.